Final report - Pulp & Paper Industry Strategy Group (Canberra, A.C.T. : Commonwealth of Australia, 2010)
"This report should not be considered a 'government' report. It is a review of the industry by the industry and has been prepared for the consideration of the Australian Government. The views and recommendations in this report should not be considered as endorsed by the Australian Government or any state government. The Australian Government is expected to respond to the report and its recommendations as appropriate."--P. xi.
"March 2010"
Includes bibliographical references.
Also available electronically. Address as at 18/5/2010: http://www.industry.gov.au/Section/Industry/Documents/PulpandPaperIndustryStrategyGroupFinalReportMarch2010.pdf.
Keywords: Pulpwood industry -- Australia; Wood-pulp industry -- Australia; Paper industry -- Australia